Biochemical and microbial changes reveal how aerobic pre-treatment impacts anaerobic biodegradability of food waste. (October 2018) - Fisgativa, Henry; Tremier, Anne; Saoudi, Mohamed; Le Roux, Sophie; Dabert, Patrick
Graphical abstract: Highlights: Biochemical and microbial modifications by aerobic pre-treatment of FW were studied. Methane potential is preserved with a 2-days aerobic pre-treatment at 21%O2 . VFA and simple carbohydrates reduction may limit acidification on subsequent dry AD. Aerobic pre-treatment promotes the presence of fungi and VFA consuming bacteria. Hydrolytic exoenzymes presence explains solubilisation of organic macromolecules. Abstract: Aerobic pre-treatment of food waste (FW) was performed at different oxygen concentrations (0%, 5%, 10% and 21%O2 ) and different durations (1, 2, 3 and 4 days) to investigate its impact on biochemical and microbial community characteristics of the waste and its ability to improve anaerobic biodegradability. Whatever the duration, the highest effect of pre-treatment was observed at full aerobic pre-treatment (21%O2 ) while 5%O2 and 10%O2 showed lower transformation performances. Biochemical variations at 21%O2 were mainly a decrease of simple carbohydrates, volatile fatty acids (VFA) and low molecular weight water soluble compounds and an increase of high weight water soluble compounds. Microbial community analysis showed a clear modification of populations after 21%O2 aerobic pre-treatment, changing from an initial dominance of lactic acid bacteria to a final dominance of VFA consumers (like Acetobacter ) and a higher presence of Fungi . Enzymatic tests showed an increase of exoenzymes content and a higher presence of protein and carbohydrates degrading enzymes. Finally, the aerobic pre-treatment did not negatively impact methane potential of FW (496 NLCH4 ·kgVS −1 ) which remained unchanged after two days of pre-treatment at 21%O2 . These latter optimal pre-treatment conditions are proposed to be tested in future investigation of anaerobic digestion (AD) process with low inoculum to substrate ratio in order to assess their ability to avoid acidification risk during AD of FW.